The Effectiveness of the PARAS Learning Model (Problems-Attention-Relevance-Assurance-Satisfaction) on the Ability to Think Geometry and Motivation for Student Achievement - Hamidah Hamidah; Zaenuri Zaenuri; Isnarto Isnarto; Arief Agoestanto; Jaka Wijaya Kusuma (Universitas Negeri Semarang, 2022)
The research was motivated by the results of previous research, namely that students only reached level 2 of Van Hiele's geometric thinking ability and the motivation for student achievement was low. So that the PARAS learning model was chosen, namely the modification of problems based learning and the ARCS model. The purpose of the study was to determine the effectiveness of the PARAS learning model on the ability to think geometry and motivation for student achievement. In this research design One-group Pretest-posttest Research Design. The population is mathematics education students of Bina Bangsa Serang University for the 2021-2022 academic year. The sample was selected using the purposive sampling technique, namely the second semester students, totaling 22 students. Data collection techniques with geometric thinking ability tests before and after learning and a questionnaire of motivation to excel after learning. The data analysisis the effect size test, percentage, chi-square test and contingency coefficient. In conclusion, it is known that the effectiveness of the PARAS learning model on students' geometry thinking ability is very high and students have been able to reach the deduction level. For the motivation for student achievement after being given learning with the PARAS learning model, it is concluded that the average is relatively high. Furthermore, it is known that there is no relationship between the motivation to excel and the student's geometric thinking ability. The implication of this study is a modified learning model that can improve the ability to think geometry and motivation for student achievement.